Kepuasan Peserta Diklat Terhadap Penggunaan Mentimeter Sebagai Metode Pembelajaran Latsar CPNS Milenial Kabupaten Kampar - Megasari, Embung (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2022)
Participants in the Basic Training for Candidates for Civil Servants at BPSDM Riau Province are millennials, attached to technology, digital learning applications, and provide satisfaction to them, in this case using Mentimeter as a learning application. In a quasi-experimental way, this study describes the perception of the participant's satisfaction scale on the use of Mentimeter as a learning application for the Millennial Generation Civil Servant Latsar Class E Class E, Kampar Regency at BPSDM Riau Province. Satisfaction scale is measured through tangibles, reliability, responsiveness, assurance, and empathy. This finding proves that as a millennial generation learning application, the satisfaction of CPNS Latsar participants with the use of Mentimeter is at the